2012
DOI: 10.1080/08975353.2012.654080
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Couple Therapy for Chronic Illnesses: Enriching the Emotional Quality of Relationships With Emotionally Focused Therapy

Abstract: Chronic illness affects couples' relationship dynamics, as well as individual functioning. A chronic illness may present a significant amount of stress for both the patient and partner. This article discusses the application of an empirically supported couples' therapy approach, emotionally focused therapy, to address relationship distress and individual functioning in the context of chronic illness.Two case examples show how couples can learn to enrich the emotional quality of their relationship; express thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…8,21,22 Patients also felt lonely when they had been rejected by their spouse or at times when they needed their spouse most. 23 There were descriptions of spouses or significant others not sharing patients' understandings or meanings, 20 or their feelings and illness situations. 23,24 Emotional loneliness was also described as resulting from transformation of the body and isolation from friends, family, and intimates.…”
Section: Loneliness In Intimate and Family Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,21,22 Patients also felt lonely when they had been rejected by their spouse or at times when they needed their spouse most. 23 There were descriptions of spouses or significant others not sharing patients' understandings or meanings, 20 or their feelings and illness situations. 23,24 Emotional loneliness was also described as resulting from transformation of the body and isolation from friends, family, and intimates.…”
Section: Loneliness In Intimate and Family Relationshipsmentioning
confidence: 99%
“…23 There were descriptions of spouses or significant others not sharing patients' understandings or meanings, 20 or their feelings and illness situations. 23,24 Emotional loneliness was also described as resulting from transformation of the body and isolation from friends, family, and intimates. 20 Parkkila et al 8 described emotional loneliness in patients when they felt they had no one close by, or anyone who would listen to them and talk to them.…”
Section: Loneliness In Intimate and Family Relationshipsmentioning
confidence: 99%
“…The only other study found was a similar type of retrospective case study using EFT in two couples, only one of which included TBI. 38 Over the course of twenty sessions, this couple eventually learned to identify their emotional cycle, underlying emotions, unmet needs, as well as restructure their interactions, share emotional experiences, and better problem-solve. These Because individuals with BI are susceptible to many challenges within the same domains as non-TBI couples, it is logical to anticipate the same focus areas for treatment would also be applicable to BI marital problems.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…57 Marital issues after BI and the need for appropriate interventions are Running Head: INTERVENTION TO IMPROVE RELATIONSHIPS AFTER BI 16 well-documented. 18 However, with exception of a few published marital intervention retrospective case studies, [37][38] the current literature on marital intervention studies in the BI population has been non-existent. In the general population literature, investigators have documented various shortcomings in marital outcome studies including lack of random allocation, use of appropriate control groups, application of appropriate statistical analyses, assessment of pre-treatment and post-treatment functioning, follow-up across subjective and objective measurements, and use of experienced therapists, to name a few.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, couples can learn to improve the emotional quality of their relationship, express their feelings to each other to expand their emotional experiences and meet each other's needs for safety and comfort, despite the limitations and challenges presented by the child's CKD. 14 Other health care for the child causes changes in the family dynamics, for example, requiring adaptations to the new dietary guidelines.…”
Section: ] (E-2)mentioning
confidence: 99%